Healthcare Sector’s Response to the Syrian Refugees Amid Lebanon’s Multi-Layered Crisis - Fakhry, Yasmine (2022)
Despite the Lebanese healthcare system showing resilience throughout its critical history, the multidimensional crisis including the Syrian refugee crisis turned this system into a very fragile and vulnerable one. The aim of this thesis is to examine health security’s fulfillment of Syrian refugees in Lebanon and their host community, and explore whether or not they fulfill the health needs of their beneficiaries’ different health coverage schemes. The study revealed that the Syrian refugee community is granted health access under terms, conditions and restrictions including OOP payment. Regarding the host community, results showed that traditional health guarantors are nearly absent, and accordingly citizens are supposed to access health services subject to nearly full OOP payments except in few cases. This study highlights the fact that the refugees are granted better and easier access to health services whereas the host citizens are subject to complicated processes for approval topped with high OOP. This finding raises “a paradox of health access” where the refugee can access health services with minimal OOP to a certain extent more than the host citizen itself.